BUSINESS PLANNING AND FINANCIAL SWOT ANALYSIS AS WAYS OF INCREASING THE EFFICIENCY OF ECONOMIC ACTIVITY OF THE UNIVERSITIES - Kovtun, O. O. (Science and Transport Progress, 2005)
In the present-day, quickly changing economical situation it is practically impossible to achieve positive results without planning one’s actions and forecasting their consequences on the market of educational and other services. A comparison of theoretical and practical approaches to organization and management of competitiveness on the market of educational services allows to propose business-planning of financial and economic activities on the basis of the method of financial SWOT-analysis and comparison of economic parameters as a way of increasing efficiency of economic activities of a university or college.